Modified Biochar From Waste Biomass (Water Hyacinth) To Treat Textile Dye Wastewater - Muhammad Sufi Shahiran, Ahmad Azmi (2023)
One of the industries with the quickest growth rate and a major contribution to Malaysia's economic expansion is the textile industry. One of the main causes of water pollution is the discharge of dyes into the environment during the dyeing and finishing procedures for textile fibres. Individual wastewater treatment, whether it be physical, biological, or chemical, is frequently quite expensive and produces a lot of sludge. In the meanwhile, water hyacinth (WH) or Eichhornia crassipes is an invasive plant that will block the water surface from letting the sunlight goes through the water, causing oxygen levels to reduced, water quality to deteriorate and ecosystem lifeforms to suffer. To filter the wastewater, a substance for the filter is needed. Thus, the use of water hyacinth as activated carbon was suggested. The water hyacinth was collected, dried undergoes pyrolysis in three different temperatures, which is 250°C, 300°C and 400°C. Then, the WH were impregnated in phosphoric acid with 2:1 ratio for chemical activation. The results were then taken and recorded. The parameter taken were Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS) and Colour ADMI. Results shown that activated carbon with 400°C has higher removal efficiency with 23% in COD, 51% in TSS and 47% for colour ADMI.